An Improved Method Of Determining The Zeta-Potential Of Mineral Particles By Micro-Electrophoresis - Sukeyuki Mori; Hisao Okamoto; Tsuyoshi Hara; Kinjiro Aso (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1980)
A theoretical calculation of the electro-osmotic circulation of liquid in a rectangular micro-electro-phoresis cell was presented by Smoluchowski (1921) and Komagata (1933). According to their theories, the velocity of liquid changes with depth such that the velocity distribution may be represented by a symmetrical parabola in the cell. Their theories appear contrary to the results of our experiments which show that the velocity distribution curve is represented by a symmetrical parabola whose symmetrical axis is displaced from the center line of the cell. A similar phenomenon had been suggested by Lane and White in 1937 based on the latter's theory which seemingly was incomplete. By using methods of measuring electrophoretic velocities based on the above three theories, serious errors are obvious. We are thus proposing a unified theory for determining the electrophoretic velocity of mineral particles in a rectangular cell. The equations of Smoluchowski, Komagata and White can be derived from our theory as special cases. On the basis of our theory, we are proposing an improved method of determining the precise electrophoretic velocity of mineral particles based solely on the coefficients of the velocity distribution curve. In our experiments, this method gives satisfactory results. We determined the relation between the zeta-potential and pH value of suspension for several minerals.